Es wird Zeit! Ansätze einer neuen Arbeitszeitdebatte in der IG Metall - Jänicke, Sophie; Ohl, Kay; Wagner, Hilde (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2008)
The article discusses the changing working time conditions in Germany. The development of trade union policies towards working time is considered and the actual concepts of the metal workers union (IG Metall) are presented.